Blood and body fluids: knowledge, attitude and practice of medical students in Ajman, UAE - Sreedharan, Jayadevan; Muttappallymyalil, Jayakumary; Venkatramana, Manda (International Journal of Occupational Safety and Health, 2013)
The health care workers should be aware of Universal Work Precaution (UWP) as there is an increased risk of exposure to infectious diseases which is considered mainly due to accidental exposure to blood and body fluids. This study mainly aims to evaluate the knowledge, attitude and practice of medical students on blood and body fluids at Gulf Medical University, Ajman, United Arab Emirates (UAE). The study subjects constituted 212 medical students of academic years 2005 – 2009. A self administered questionnaire was utilized for data collection and analysis was performed using statistical software PASW 17. Results: The participant’s age ranged from 17 to 27 years. A statistically significant association (P<0.001) between knowledge on UWP and year of study was observed, with a highest knowledge of 95.5% in third year, 88% fifth year, 82.5% fourth year, 67.3% second year and a lowest of 33.3% in first year. A statistically significant association was obtained between knowledge and practice (P<0.01) of medical students regarding needle recapping. The study reported, that a majority of participants with the opinion on wearing surgical aprons, masks and protective goggles during surgery while the practice was not up to the level of knowledge. Statistically significant association was obtained between knowledge and practice (P<0.01) with regard to the usage of surgical aprons and protective goggles. The present study thus indicates an increase in practice with increase in knowledge. The study also emphasizes the need for providing proper education on transmission of blood-borne infections, standard precautions and increasing availability of protection strategies. DOI: http://dx.doi.org/10.3126/ijosh.v3i1.5981 International Journal of Occupational Safety and Health, Vol 3 No 1 (2013) 5-10